2016
DOI: 10.1039/c6ra18185f
|View full text |Cite
|
Sign up to set email alerts
|

Facile in situ synthesis and characterization of a novel PANI/Fe3O4/Ag nanocomposite and investigation of catalytic applications

Abstract: A novel magnetic hybrid nanocomposite was successfully synthesized via in situ polymerization, well characterized by FT-IR, XRD, EDX and FE-SEM analysis, and its catalytic activity shown in the synthesis of pharmaceutically important pyrans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Previously, Rabbani et al 80 reported efficient removal of MB using catalysts of Ag–TiO 2 and Zn‐TCPP/Ag–TiO 2 under UV and visible light irradiation. They found that both synthetic catalysts have higher catalytic activity under UV light than the visible light and removal efficiency of MB reaches the maximum value of 100% for both catalysts 81–85 . Table shows the maximum removal of adsorption and photodegradation of MB by some catalyst 86–90 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Rabbani et al 80 reported efficient removal of MB using catalysts of Ag–TiO 2 and Zn‐TCPP/Ag–TiO 2 under UV and visible light irradiation. They found that both synthetic catalysts have higher catalytic activity under UV light than the visible light and removal efficiency of MB reaches the maximum value of 100% for both catalysts 81–85 . Table shows the maximum removal of adsorption and photodegradation of MB by some catalyst 86–90 …”
Section: Resultsmentioning
confidence: 99%
“…They found that both synthetic catalysts have higher catalytic activity under UV light than the visible light and removal efficiency of MB reaches the maximum value of 100% for both catalysts. [81][82][83][84][85] Table 5 shows the maximum removal of adsorption and photodegradation of MB by some catalyst. [86][87][88][89][90]…”
Section: Removal Of Mb Using Synthetic Cu 2 Omentioning
confidence: 99%
“…[6][7][8][9][10][11] The agglomeration of nanoparticles during the catalytic reaction is one of their disadvantages. [12][13][14][15][16] Separation of nanoparticles from the reaction medium using simple methods such as filtration and centrifugation is difficult. [17][18][19][20] To overcome these difficulties, different solid supports such as TiO 2 , graphene, mesoporous materials, and Fe 3 O 4 were applied for the immobilization of metal nanoparticles and the construction of the heterogeneous nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Among conducting polymers, polyaniline (PANI) is one of the most preferred conjugated polymers due to its low price and availability, easy synthetic procedure, tolerance to a wide range of reaction conditions and interesting redox properties associated with the nitrogen atom in the polymer backbone. Polyaniline has been used as a support material because of its unique properties such as easy synthesis from readily available starting material (aniline), higher stability and non‐solubility in common organic solvents . Some of the reported PANI based catalysts used for various organic transformations such as Mizoroki‐Heck Cross‐Coupling reaction, methanol oxidation, epoxidation of peptides, epoxidation of alkene, Biginelli reaction, and oxidation of alcohols are given in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline has been used as a support material because of its unique properties such as easy synthesis from readily available starting material (aniline), higher stability and non-solubility in common organic solvents. [7] Some of the reported PANI based catalysts used for various organic transformations such as Mizoroki-Heck Cross-Coupling reaction, [8] methanol oxidation, [9] epoxidation of peptides, [10] epoxidation of alkene, [11] Biginelli reaction, [12] and oxidation of alcohols [13] are given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%